Towards the Burden of Human Leptospirosis: Duration of Acute Illness and Occurrence of Post-Leptospirosis Symptoms of Patients in The Netherlands - Goris, Marga G. A. (Public Library of Science, 2013)
BACKGROUND: Leptospirosis is a global zoonotic disease. Although important for the assessment of the burden of leptospirosis, data on the duration of the illness and the occurrence of post-leptospirosis complaints are not well documented. Hence the main objective of this study was to estimate the occurrence of persistent complaints and duration of hospital stay in laboratory confirmed leptospirosis patients in the Netherlands during 1985 to 2010. Additionally, several risk factors potentially impacting on the occurrence of post-leptospirosis complaints were investigated. METHODS/PRINCIPAL FINDINGS: The duration of the acute phase of leptospirosis was 16 days (IQR 12–23); 10 days (IQR 7–16) were spent hospitalized. Eighteen fatal cases were excluded from this analysis. Complaints of leptospirosis patients by passive case investigations (CPC) derived from files on ambulant consultations occurring one month after hospital discharge, revealed persistent complaints in 108 of 236 (45.8%) laboratory confirmed cases. Data on persistent complaints after acute leptospirosis (PCAC), assessed in 225 laboratory confirmed leptospirosis cases collected through questionnaires during 1985-1993, indicated 68 (30.2%) PCAC cases. Frequently reported complaints included (extreme) fatigue, myalgia, malaise, headache, and a weak physical condition. These complaints prolonged in 21.1% of the cases beyond 24 months after onset of disease. There was no association between post-leptospirosis complaints and hospitalization. However, individuals admitted at the intensive care unit (ICU) were twice as likely to have continuing complaints after discharge adjusting for age and dialysis (OR 2.0 95% CI 0.8-4.8). No significant association could be found between prolongation of complaints and infecting serogroup, although subgroup analysis suggest that infection with serogroups Sejroe (OR 4.8, 95%CI 0.9-27.0) and icterohaemorrhagiae (OR 2.0, 95%CI 0.9-4.3 CI) are more likely to result in CPC than infections with serogroup Grippotyphosa. CONCLUSION/SIGNIFICANCE: In addition to the acute disease, persistent complaints have an impact on the burden of leptospirosis.